Effect of Profitability, Capital Intensity, Leverage, Sales Growth, and Company Size on Tax Avoidance - Endah Fitri Ana Rahayu; Siti Nurlaela; Sari Kurniati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
This research was conducted to test and analyze the effect of profitability, capital intensity, leverage, sales growth, and company size on tax avoidance. The data source used is secondary data obtained from the financial reports of mining companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The population of this study is mining companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. Sampling using purposive sampling method and obtained samples used in this study amounted to 18 companies. The data analysis technique used multiple linear regression analysis which was processed with SPSS version 25. The results showed that leverage and sales growth had an effect on tax avoidance. While profitability, capital intensity, and firm size have no effect on tax avoidance.